(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Effective postoperative pain control in children undergoing lower abdominal surgery remains challenging because systemic opioids may cause adverse effects such as nausea, vomiting, sedation, and respiratory depression. Landmark -guided transversus abdominis plane (TAP) block is an established regional analgesic technique for abdominal wall pain. Dexamethasone has been investigated as an adjuvant to local anesthetics to prolong block duration and improve analgesic quality. This study evaluated whether adding dexamethasone to ropivacaine in landmark -guided TAP block improves postoperative analgesia in pediatric patients undergoing lower abdominal surgery. Aims and Objectives: The aim of this study is to compare the efficacy of Ropivacaine and Ropivacaine with Dexamethasone in Transversus Abdominis Plane (TAP) block in pediatric patients undergoing lower abdominal surgery and to compare duration of postoperative analgesia, postoperative hemodynamic parameter and incidence of side effects between the two groups. Material and Methods: In this prospective, randomized, double-blind study, 60 pediatric patients aged 1–12 years with American Society of Anesthesiologists physical status I–II scheduled for elective lower abdominal surgery under general anesthesia were randomly assigned to two groups. Group R received TAP block with 0.2% ropivacaine 0.5 mL/kg plus saline, and Group RD received 0.2% ropivacaine 0.5 mL/kg plus dexamethasone. The primary outcome was time to first rescue analgesia. Secondary outcomes included postoperative pain scores, total rescue analgesic consumption, hemodynamic variables, and adverse events. A two-sided P value < 0.05 was considered statistically significant. Results: The mean time to first rescue analgesia was significantly longer in Group RD than in Group R (525.85 ± 81.30 min vs. 243.00 ± 97.36 min, P < 0.001). Postoperative pain scores were significantly lower in Group RD at 4 h, 6 h, and 12 h after surgery (P < 0.05). Total rescue analgesic consumption during the first 24 h was significantly reduced in Group RD compared with Group R (P < 0.001). Heart rate, mean arterial pressure, and oxygen saturation were comparable between groups at all measured time points (P > 0.05). No serious adverse events, local anesthetic toxicity, or block-related complications were observed. Conclusions: Adding dexamethasone to ropivacaine in landmark -guided TAP block significantly prolonged postoperative analgesia and reduced postoperative analgesic requirements without increasing adverse effects. This combination may be an effective component of multimodal analgesia for pediatric lower abdominal surgery.